Pengembangan Media Pembelajaran Matematika Berbasis Muvizu di Kelas 2 Sekolah Dasar - Siti Azizah (Universitas Indraprasta PGRI, 2016)
The aim of this research was to design and develop media on learning mathematics based on Mavizu in the Second Grade of Elementary School, the material is about multiplication and division until two numbers in the second semester. The method of the research used Research and Development, especially research development by ADDIE method. The first steps of this research development analysed the need, made a plan, then created the media learning animation movie in 3D, and was tested by the expert. Based on the result of the test experiment, needed the revision. The result of the research shows that media which was developed, fulfilled the requirement as a media learning animation movie in 3D that the material is about multiplication and division until two numbers. The conclution can be seen based on the test experiment by the expert.